Knowledge infrastructure and higher education in India - Lal, Kaushalesh; Paul, Shampa (London Routledge, 2021)
This short book examines the availability and adoption of new education technologies in higher education institutions in India. It provides a summary of the activities in which such technologies are being used and the catalytic factors for such adoptions. The book also evaluates the impact on skill development, and will be a useful reference for those who are interested to find out more about technology adoption and implementation in higher education, and what the challenges are through the learning experiences in these education institutions.
Keywords: Infrastructure Sector; Higher Education in India; Knowledge Infrastructure